2016
DOI: 10.1007/s10528-016-9766-5
|View full text |Cite
|
Sign up to set email alerts
|

Taq1B Polymorphism of Cholesteryl Ester Transfer Protein (CETP) and Its Effects on the Serum Lipid Levels in Metabolic Syndrome Patients

Abstract: The metabolic syndrome (MetS) is one of the most important risk factors for type 2 diabetes and cardiovascular disease. This syndrome is characterized by abdominal obesity, hypertension, insulin resistance, and dyslipidemia. The plasma origin of Cholesteryl ester transfer protein (CETP) is responsible for transferring cholesterol esters from high-density lipoprotein particles to apolipoprotein B containing lipoproteins compartment. We conducted this study to investigate the association between CETP gene Taq1B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
1
6
1
Order By: Relevance
“…This is consistent with Anton et al [36] who hold that the risk of MS was reduced by 32% ( p = 0.005, OR = 0.68) in carriers of the B 2 variant. However, this was different from observations by Jeenduang [38] and Maroufi [39]. …”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with Anton et al [36] who hold that the risk of MS was reduced by 32% ( p = 0.005, OR = 0.68) in carriers of the B 2 variant. However, this was different from observations by Jeenduang [38] and Maroufi [39]. …”
Section: Discussioncontrasting
confidence: 99%
“…Multivariate analysis the relationship remained significant (OR = 2.82 [95% CI 1.07-7.41], p = 0.036), despite the relationship rs1800775 polymorphism between cases (MS obese) and non-MS obese is not significant. A study of Maroufi et al found that CETP levels were significantly higher in the adult MS group (1.64 ± 0.32 µg/mL) than healthy controls (1.53 ± 0.34 µg/mL) [23]. In this study, CETP levels in MS obese groups and non-MS obese (2.49 ± 1.03 µg/mL vs. 2.04 ± 0.92 µg/mL) were higher than the previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to the present study, however, Heilbronn et al reported that BMI was higher in obese B1B2 participants, compared to obese subjects with B1B1 and B2B2 (33). Marou et al reported that Taq1B polymorphisms had no effect on related metabolic syndrome parameters, including WC (34). Also, some studies have shown that CETP polymorphism is not associated with anthropometric parameters (35,36).…”
Section: Discussionmentioning
confidence: 99%